Perlindungan Hukum terhadap Hak Pasien pada Pelayanan Kesehatan di Puskesmas Baqa - Muhamad Agus Sariyansah; Sunariyo; Surahman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Health services are a basic need guaranteed by the state, including legal protection for patients as part of human rights. Law No. 17 of 2023 on Health affirms patients’ rights to safe, high-quality, and non-discriminatory services, while requiring health facilities to conduct regular accreditation and provide effective complaint mechanisms. However, in practice, many patient rights violations still occur, especially in community health centers (puskesmas), due to limited resources, inadequate infrastructure, and low awareness among both patients and health workers. This study employs a normative-empirical legal method through interviews, observations, and literature review at Puskesmas Baqa, Samarinda. Findings show that Standard Operating Procedures (SOPs) serve as guidelines for health workers and reflect preventive legal protection, though challenges remain such as heavy workloads, insufficient training, and limited facilities. Repressive protection is implemented through complaint mechanisms and accountability of health workers. The integration of Islamic values such as hifz al-nafs (protection of life), justice, trustworthiness, honesty, and compassion strengthens substantive legal protection, ensuring that it is not only based on compliance with regulations but also reflects ethics and humanity in health services. The study concludes that patient protection at Puskesmas Baqa aligns with Law No. 17 of 2023, but requires reinforcement through improved SOPs, facilities, training, and legal literacy